Impacto das mudanças climáticas na resistência de clones de eucalipto a Ceratocystis fimbriata - Favalessa, Marcilene (2014)
Eucalyptus is one of the commercially important tree species grown in several countries in the world with wide environmental adaptability, representing major source of financial resources for the economy of Brazil. The wilting of Ceratocystis fimbriata in Eucalyptus is one of the diseases that limit the growth and crop productivity. The pathosystem, as well as their interactions can be affected by global climate change, particularly with respect to changes in temperature and carbon dioxide (CO2). In this context, the aim of this study was to analyze the effect of increased CO2 concentration and temperature on the behavior of two eucalyptus clones with different levels of resistance to Ceratocystis fimbriata. The study was conducted in growth ("phytotron") of the Laboratory of Ecophysiology and Forest Meteorology in the Department of Forest Science and Wood Center for Agricultural Sciences, Federal University of Espírito Santo chamber, located in the town of Jeromino Monteiro, ES. Eucalyptus seedlings with different degrees of resistance to the pathogen were used in the initial phase transplanted to pots 12L and staying in a greenhouse for 45 days and then inoculated with the pathogen and maintained in "phytotron" for 30 days. The experiment was conducted in two scenarios with different environmental conditions, where the simulated temperature increase according to data from scientific paper, for the northern region of the state of Espirito Santo. The current scenario was developed with temperature ranging from 18 to 30 ° C and CO2 concentration of 400 µmol.mol-1 and the future scenario with temperatures ranging from 22 to 34°C and CO2 concentration of 800 µmol.mol1. Growth characteristics were quantified by measuring height, diameter, leaf area and plant dry matter. To characterize the ecophysiological responses of gas exchange measurements were performed. The experimental design was completely randomized (DIC) in a 3x2 factorial design, with three clones and two scenarios, the averages were significant when subjected to Tukey's test to compare the level of 5% probability. For those genetic materials eucalyptus evaluated, the high concentration of CO2 and temperature on the future scenario, acted as a stressor for eucalyptus seedlings, where it was possible to notice that the seedlings subjected to this scenario had significantly lower total dry mass, leaf area, shoot height and net photosynthesis. As the severity of the disease, the clone susceptible inoculated had the disease in the two scenarios under study, since the clone resistant showed different behavior when comparing the two scenarios studied, observing the disease only in the seedling of the future scenario. Based on the results of this research, it is believed that climate change should alter the conditions of resistance of Eucalyptus plants by increasing the intensity of the disease.